Analisis Kinerja Keuangan Ditinjau Dari Pendekatan Economics Value Added (EVA) Dan Market Value Added (MVA) PT. Rajawali Nusantara Indonesia (Persero) - Niki Kosasih (CITRA EKONOMI, 2020)
The study aims to find out : (1) To determine the condition of the financial performance ot PT. Rajawali Nusantara Indonesia (Persero) viewed from short Economics value added, (2) To determine the condition of the financial performance of PT. Rajawali Nusantara Indonesia (Persero) seen from market value added, (3) To Analyze the condition of PT. Rajawali Nusantara Indonesia (Persero), this type of research is academic research. The analysis tool used in this study uses financial ratios. Based on the results of the above research, it can be seen the condition of the financial performance of PT. Rajawali Nusantara Indonesia (Persero) through the EVA approach, which in 2012 amounted to 538.895.600 shows that the condition of financial performance is healthy, in 2013 amounted to 1.446.588.000 indication that the condition of healthy financial performance, in 2014 amounted to – 164.001.000 indication that the condition of financial performance unhealthy, in 2015 amounted to – 1.132.748.100 indication that the condition of financial performance is unhealthy, and in 2016 amounting to – 1.584.975.000indicated that the condition of financial performance is unhealthy. The condition of the financial performace PT. Rajawali Nusantara Indonesia (Persero) through the MVA approach, which in 2012 amounted to 4.117,99 shows that the condition of financial performance is good, in 2013 amounting to 4.533,54 indicates that the condition of financial performance is good, in 2014 amounted to 4.135.00 indicatesing that the condition of financial performance was good, at in 2015 amounting to 4.073.94 indicates that the condition of financial performance is good, and in 2016 amounting to 7.210.01 indicates that the condition of financial performance is good.